2015
DOI: 10.1002/jmr.2474
|View full text |Cite
|
Sign up to set email alerts
|

IgG abzymes with peroxidase and oxidoreductase activities from the sera of healthy humans

Abstract: We present the evidence showing that small fractions of electrophoretically homogeneous immunoglobulin G (IgGs) from the sera of healthy humans and their Fab and F(ab)2 fragments oxidize 3,3'-diaminobenzidine through a peroxidase activity in the presence of H2 O2 and through an oxidoreductase activity in the absence of H2 O2 . During purification on protein G-Sepharose and gel filtration, the polyclonal IgGs partially lose the Me(2+) ions. After extensive dialysis of purified Abs against agents chelating metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(84 citation statements)
references
References 47 publications
(164 reference statements)
2
82
0
Order By: Relevance
“…Interestingly, the same activities were detected in IgG from the blood of healthy people [120,121]. The relative peroxidase activity of IgG of healthy people in the absence of external metal ions varies very much from donor to donor, but on average, it is about five times lower than in rat IgGs [120,121].…”
Section: Abzymes With Oxidation-reduction Activitiesmentioning
confidence: 67%
See 2 more Smart Citations
“…Interestingly, the same activities were detected in IgG from the blood of healthy people [120,121]. The relative peroxidase activity of IgG of healthy people in the absence of external metal ions varies very much from donor to donor, but on average, it is about five times lower than in rat IgGs [120,121].…”
Section: Abzymes With Oxidation-reduction Activitiesmentioning
confidence: 67%
“…Оnly 17% of rat IgGs were shown to possess catalase activity. It was shown that small fractions of IgGs and their F(ab) 2 and Fab fragments of IgGs from sera healthy humans oxidize 3,3′-diaminobenzidine in the presence of H 2 O 2 through a peroxidase and in the absence of H 2 O 2 through an oxidoreductase activity [120,121].…”
Section: Abzymes With Oxidation-reduction Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…From 26 to 39% of rat IgGs can interact with less or more efficiently with different metals ions. Interestingly, chromatography of IgGs from human plasmas on Chelex non-charged with metal ions led to the binding of a small amount of IgGs (~ 5%) bound with metal ions [36]. Chelex charged with Cu 2+ ions additionally adsorbed ~ 38% of the total IgGs.…”
Section: Trace Elements -Human Health and Environmentmentioning
confidence: 99%
“…It was demonstrated that small fractions of IgGs from the sera of healthy humans as well as their Fab and F(ab) 2 fragments oxidize DAB through peroxidase and oxidoreductase activities [36]. In contrast to rat antibodies, IgGs from human blood have both the dependent and independent on metal ions activities.…”
Section: Trace Elements -Human Health and Environmentmentioning
confidence: 99%